An efficient model for solar radiation induced top displacement of steel-concrete composite bridge towers. (June 2023) - Zhang, Han-Shuo; Liu, Yu-Fei; Li, Hong-Tao; Nie, Jian-Guo; Fan, Jian-Sheng; Liu, Cheng
Abstract: The temperature effect caused by solar radiation significantly influences the stress state of bridges. Especially for ultra-high bridge towers, considerable deformation induced by solar radiation affects the safety of the structures. This research is conducted to evaluate the temperature deformation of a steel–concrete composite bridge tower where a sliding saddle is adopted. First, the temperature distribution pattern of the structure is analyzed. Second, based on the temperature distribution, an efficient model which can be applied to the long-term calculation is established, aiming at directly calculating the deformation results. Then, an outdoor experiment study is carried out to verify the temperature distribution and the results of sectional curvature. Finally, the efficient model is applied to calculate the annual bidirectional deformation. This method realizes the long-term temperature effect evaluation of the structure before construction, and the results can be referred to as guidance for the analysis of related types of structures.